Isolation and characterization of acetylated LM-pectins extracted from okra pods. (January 2015) - Alba, K.; Laws, A.P.; Kontogiorgos, V.
Abstract: Pectin was isolated by aqueous extraction at pH 6.0 or 2.0 from okra ( Abelmoschus esculentus L.) pods. An isolation protocol was designed to extract pectin and to study the influence of the extraction pH on their composition and physicochemical properties. The extracted pectin was assessed using sugar compositional analysis (neutral sugars, galacturonic acid, acetyl and methyl contents). FT-IR and NMR spectroscopy, size exclusion chromatography (SEC) and dilute solution viscometry were also used to determine the macromolecular characteristics of isolated pectin. The extraction protocols resulted in the isolation of pectin of high purity as evidenced by their high total carbohydrate (70.0–81.8%) and low protein (4.3–6.3%) contents. Samples contained between 46 and 56% galacturonic acid, had broad molecular weight distributions, a low degree of methylation (40.0 and 24.6%) and high degree of acetylation (52.2 and 37.6%). Neutral sugar analysis showed that the pectin extracted at pH 6.0 contained more neutral sugars, particularly, galactose (21.7–25.7 mol%), rhamnose (10.1–13.2 mol%) and arabinose (7.1–7.3 mol%) than that extracted at pH 2.0 indicating variations in fine structure. In addition, molecular parameters of the isolated pectins, such as intrinsic viscosity (2.8–4.4 dL g −1 ), critical concentration (0.15–0.45 dL g −1 ) and coil overlap parameter (0.66–1.51), showed that extraction conditions resulted in pectin with different chain morphology. The yield and physico-chemical characteristics of the extracted pectin from okra pods were influenced by the extraction conditions. Graphical abstract: Highlights: Isolation protocol was design to extract pectins from okra. Low methoxyl, highly acetylated pectins were extracted. Complete chemical and physicochemical characterization was performed.